“El Alacrán” (2017)
This work has been carried out through the systematization of experiences, its purpose is object of study the process of accommodation of a text whose genre is theater historical “El AlaKráN”. (Camilo Ramírez Triana, 2004), which made it possible to demonstrate different processes of understanding the transformation that a text must undergo to be represented, seeking to generate a staging that respected the proposal of the author and in turn allowed us to make the work understandable and close to the public contemporary and for the members of the group that developed the joint assembly.